Validation and determination of equations prediction weight for Ibero-American horses in Costa Rica - Solano-Mora, Grethel; WingChing-Jones, Rodolfo (Agronomía Mesoamericana, 2019)
Introduction. A limitation in production systems is the weighing of animal, an activity that is performed empirically or with the use of weight estimation tapes which generate overestimates. Objective. The objective was to validate fourteen weigh predictive equations in Ibero-American horses, and develop the breed’s own equations for Costa Rica. Material and methods. The investigation was carried out between the months of September 2016 and March 2017. Allometrics measurements of weight (kg), length (cm), height at the withers (cm), thoracic perimeter (cm), umbilical perimeter (cm), and age (months) of 152 animals (male and female) registered in the Asociación Centroamericana de Criadores de Caballos de raza iberoamericana, were taken. As a result on the analysis of the information, a growth curve was developed for males (y= 94.54 ln(X) 6 47.14; R2=0.858) and females (y=82.09 ln(x)+86.81; R2=0.744). Results. From the equations evaluated, it was determined that twelve allowed to predict the weight of the animal when it is a colt (p<0.05), five when it is considered young (p<0.05), six when it is in the process of dressage (p<0.05), and six it when it is adult (p<0.05).According to the equation used, weight overestimates of animals between 29.84kg and 168.17kg live weight were determined. Similarly, the developed equations make use of the body measurements and age of the animals, with overestimates of weight between 0.67 and 2.17 kg per animal, which allowed having a better weight prediction and thus improving the determination of the nutritional requirements, dosages of veterinary products, and the handling of the animals. Conclusion. Two equations were generated to estimate the weight of the Ibero-American horses, as well as discarding the equations available in the literature, which did not allow an estimation of the weight according to the productive stage of the animal.